2021
DOI: 10.3389/fendo.2020.615957
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Ovarian Hyperstimulation Syndrome (OHSS) Severity in Women With Polycystic Ovary Syndrome Undergoing IVF/ICSI

Abstract: IntroductionAge, polycystic ovary syndrome (PCOS), low body mass index (BMI), high antral follicle count (AFC), increased anti-Muller hormone (AMH) levels, and elevated serum estradiol (E2) concentrations are risk factors for ovarian hyperstimulation syndrome (OHSS). However, data on the relationship between risk factors and OHSS severity in patients with PCOS are rare.ObjectiveThis retrospective study examined the risk factors for OHSS and their effect on OHSS severity in patients with PCOS undergoing in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 33 publications
2
41
0
2
Order By: Relevance
“…It has been estimated, among the females receiving IVF-ET in clinical, the prevalence of mild was approximately 20% to 33%, and the moderate or severe females was nearly 3% to 8% [ 5 ]. Females with a high ovarian response, such as ovulation disorders and polycystic ovary syndrome (PCOS), as well as young age and low body mass index, are associated with an increased risk of OHSS [ 6 ]. For decades, human chorionic gonadotropin (hCG), which induces luteinization of granulosa cells and triggers final oocyte maturation, has been widely used in COH.…”
Section: Introductionmentioning
confidence: 99%
“…It has been estimated, among the females receiving IVF-ET in clinical, the prevalence of mild was approximately 20% to 33%, and the moderate or severe females was nearly 3% to 8% [ 5 ]. Females with a high ovarian response, such as ovulation disorders and polycystic ovary syndrome (PCOS), as well as young age and low body mass index, are associated with an increased risk of OHSS [ 6 ]. For decades, human chorionic gonadotropin (hCG), which induces luteinization of granulosa cells and triggers final oocyte maturation, has been widely used in COH.…”
Section: Introductionmentioning
confidence: 99%
“…The reason may be that AMH concentration correlates significantly with the number of sinusoidal follicles in the ovary before ovulation and the number of oocytes collected after treatment, and patients with high ovarian response have higher AMH concentration compared with patients with normal ovarian response. Not only that, AMH was regarded as an excellent predictor of high ovarian response and could identify the risk of OHSS better than AFC, which may be due to the fact that AMH has more stable periodicity and is less susceptible to exogenous steroid hormones; moreover, AFC requires skilled ultrasound operators to carefully identify, measure, and count ovarian eggs, probably resulting in more interobserver variability in AFC [7,18,[21][22][23][24][25]. However, few studies have analyzed the association between P level on HCG day and high ovarian response.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a secondary analysis of the Pregnancy in PCOS II trial found that higher baseline AMH level predicted poorer response to ovulation induction during treatment with oral medications (99). During in vitro fertilization, a higher AMH level has also been linked to an increased risk of OHSS in the setting of gonadotropin stimulation (100). The AMH level for a PCOS fertility patient may therefore enhance a clinician's ability to provide personalized decisions during the treatment course.…”
Section: Do: Consider Amh Levels When Treating Infertility In Pcosmentioning
confidence: 99%